Sensitive Immunoassay Detection of Plasmodium Lactate Dehydrogenase by Inductively Coupled Plasma Mass Spectrometry - Mu, Jianbing; Yu, Lee L.; Wellems, Thomas E. (Frontiers in Cellular and Infection Microbiology, 2021)
Rapid, reliable, and sensitive detection of Plasmodium infection is central to malaria control and elimination. Many Malaria Rapid Diagnostic Tests (RDTs) developed for this purpose depend upon immunoassays that can be improved by advances in bound antibody sensor technology. In a previous study, immuno-polymerase chain reaction (PCR) was shown to provide highly sensitive detection of Plasmodium falciparum lactate dehydrogenase (PfLDH) in monoclonal antibody (mAb) sandwich assays. Here, we show comparably high immunoassay sensitivity by inductively coupled plasma mass spectrometry (ICP-MS) detection of gold nanoparticles (AuNPs). Following capture of PfLDH with the primary mAb and binding of the AuNP-labeled detection mAb, ICP-MS signals from the AuNPs provided quantitative measures of recombinant PfLDH test dilutions and P. falciparum-infected erythrocytes. A detection limit of 1.5 pg/mL was achieved with the PfLDH protein. Parasitemia in cultures of P. falciparum-infected erythrocytes could be detected to a lower limit of 1.6 parasite/μl (p/μl) for early ring-stage forms and 0.3 p/μl for mixed stages including mature trophozoites and schizont-stages. These results show that ICP-MS detection of AuNPs can support highly sensitive and accurate detection of Plasmodium infection.